SARS-CoV-2 seroprevalence and social inequalities in different subgroups of healthcare workers in Rio de Janeiro, Brazil - Roberta Fernandes Correia; Ana Carolina Carioca da Costa; Daniella Campelo Batalha Cox Moore; Saint Clair Gomes Junior; Maria Paula Carneiro de Oliveira; Maria Célia Chaves Zuma; Rômulo Gonçalves Galvani; Wilson Savino; Adriana Cesar Bonomo; Zilton Farias Meira Vasconcelos; Elizabeth Artmann (Elsevier, 2022)
Summary: Background: COVID-19 has exacerbated health inequalities worldwide. Yet, such a perspective has not been investigated in specific healthcare workers and their resulting inclusion as a priority group for vaccination have been an important focus of political and social discussion. This study aimed at investigating whether SARS-CoV-2-seropositivity in healthcare workers in a public hospital in Rio de Janeiro, Brazil, was influenced by social determinants of health and the social vulnerability in subgroups of workers. Methods: A serological survey was conducted in 1,154 healthcare workers in June and July 2020. The association between the serological test results for detection of IgG antibodies to SARS-CoV-2 and socioeconomic, occupational characteristics and transportation used by the workers to commute was assessed using the Pearson´s chi-square test and Cramer's V. Findings: Overall, the serum prevalence for the virus in the healthcare workers was 30% (342/1141). Non-white workers (208/561) with lower income (169/396) and schooling (150/353), as well as users of the mass transportation system (157/246) showed the highest infection rates. Importantly they mostly corresponded to hospital support workers (131/324), in particular the cleaning personnel (42/70). Accordingly, income, schooling and work modality appeared as negative predictors, as ascertained by forest plot analysis. Interpretations: The data clearly illustrate the inequality in SARS-CoV-2 infection in the Brazilian population, comprising even healthcare workers of the Brazilian unified health system.